The Missing Scripture - Johnson, D. Lynn (Journal of Book of Mormon studies, 1994)
During his visit to the Nephites, the Savior instructed Nephi to add to their records a missing scripture concerning the resurrection of many of the dead immediately following his own resurrection, and their appearance to many people. There is good evidence that it was Samuel the Lamanite's prophecy of this resurrection that was missing. Aspects of the manner of recording, abridgment, and translation of the text of the Book of Mormon are elucidated through this missing scripture as it appears in the English text.